The influence of digital marketing and brand image on customer loyalty through customer satisfaction as an intervening variable on fashion money alter PT. Mae Abadi Evolusi Bogor City - Dwi Gemina; Yulianingsih Yulianingsih; Desi Fitria Ningsih (Universitas Nusa Cendana, 2026)
This study examines customer loyalty toward Money Alter fashion products produced by PT Mae Abadi Evolusi in Bogor by investigating the influence of digital marketing and brand image, with customer satisfaction serving as a mediating variable. A descriptive quantitative approach was employed in this research, involving 150 respondents. Path analysis was used to assess both the direct and indirect relationships among the variables under study. The findings indicate that digital marketing and brand image have a positive and significant effect on both customer satisfaction and customer loyalty. Furthermore, customer satisfaction plays an important role in enhancing customer loyalty, highlighting its significance in fostering long-term customer relationships. Customer satisfaction was also found to effectively mediate the relationship between digital marketing, brand image, and customer loyalty. It can therefore be concluded that effective digital marketing strategies and a strong brand image contribute to the enhancement of customer loyalty through increased customer satisfaction. These findings emphasize the importance of integrating digital marketing practices and brand management to strengthen customer retention and achieve a competitive advantage in the fashion industry. Keywords: Digital Marketing; Brand Image; Customer Loyalty; Customer Satisfaction